Cultural differences in the response conduct to personality inventories - Claudia Sălceanu,; Sandu, Mihaela Luminita; Cosmina Georgiana Olteanu, (Technium Social Sciences Journal, 2020)
Response styles in psychological assessment and research have been identified as an important threat to the validity of the research and to the level of confidence that a research may have. This can represent a problem namely in an intercultural research, due to the fact that individuals from different cultures may use different response scales in different ways. A sample of 90 participants, 45 Romanian and 45 Korean, aged between 28 and 55 years of age, have been assessed with The Eysenck Personality Questionnaire (EPQ) and with California Personality Inventory (CPI). The main objective was to identify significant cultural differences regarding the response conduits of the participants. Based on this objective we emitted the following hypotheses: (1) we presume there are significant differences in social desirability regarding self-control between Romanian and Korean subjects; (2) we presume there are significant differences in the Lie Scale regarding responsibility and the level of study of the participants; (3) we presume there are significant differences between self-image management between Romanian and Korean subjects; (4) we presume there are significant differences between social conformism between Romanian and Korean subjects. All hypotheses were confirmed. Results are discussed based on the importance of the cultural factor in human behaviour.